A cost-effective optimization model of safety investment allocation for risk reduction of domino effects. (September 2022) - Guo, Xiaoxue; Ding, Long; Ji, Jie; Cozzani, Valerio
Highlights: Cost-effective safety investment optimization model for domino effect risk reduction. "R_minmax" uncertain decision criterion for the optimal risk reduction strategy. Consider both preventive and mitigating measures in the optimization model. The optimal investment and its priority allocation strategy. Decision-making support for safety investment allocation of domino effects. Abstract: In general, the allocation strategy of safety measures in the domino effect is based on technical standards or simplistic rules of thumb, often leading to a subjective and uncertain decision-making process. In this work, a cost-effective risk reduction optimization model is proposed to objectively allocate the safety investment concerning domino effects in view of the risk and economic cost. Different from previous safety barrier performance assessments, we directly relate risk to economic cost through mathematical functions to trade off the economic effectiveness and domino effect risk under lower uncertainty. Not only mitigating measures, but also preventive measures are considered for domino risk reduction in the decision-making process of safety investment allocation in practical applications. The results from the case study demonstrate that the proposed model can help decision makers to identify the optimal safety investment among different investments and find the optimal investment allocation strategy given a specific economic investment in the worst-case domino scenario.